Religious vs. Practical Motivation: The Dominant Factor in Generation Z's Adoption of Sharia Fintech - Muh. Dzulfikar Izzaturrahman; Nisrina Anggi Syahputri; Heni Prasetyo (CV. Civiliza Publishing, 2025)
Despite the growing use of Sharia-compliant financial technology (fintech) services, their adoption rate among the younger generation remains relatively low, especially in Islamic universities with a strong religious culture. This study aims to analyze the dominant factors influencing the adoption of Sharia-compliant financial technology (fintech) services among students at the Faculty of Islamic Economics and Business (FEBI) at UIN Ponorogo, specifically the relationship between religious motivation and practical considerations. Using a qualitative approach with phenomenological methods, data were obtained through in-depth interviews with students who have understood or used Sharia-compliant fintech services. The results show that although students have a high level of religious awareness, practical aspects such as ease of use, cost efficiency, and service features remain primary considerations in their decisions. Furthermore, pragmatic motives were identified, with students using Sharia-compliant fintech for rational reasons such as service integration and system convenience. Partial and selective adoption also emerged as common patterns, reflecting that loyalty to Sharia-compliant fintech has not yet been fully established. The implications of this study underscore the importance of enhancing service quality, providing Sharia-compliant financial literacy education, and ensuring transparency in Sharia compliance to promote wider adoption among Generation Z Muslims.